Warning: foreach() argument must be of type array|object, bool given in /var/www/html/web/app/themes/studypress-core-theme/template-parts/header/mobile-offcanvas.php on line 20

(a) The conjunction of \(n\) formulas \(p_{1}, p_{2}, \ldots, p_{n}\) is defined to be the formula \(\left(\ldots\left(\left(p_{1} \wedge p_{2}\right) \wedge p_{3}\right) \wedge \ldots\right) \wedge p_{n} .\) For \(n=0,\) there is a special case: The conjunction of zero formulas is defined to be \(T\). For \(n=1\), that conjunction simplifies to \(p_{1}\). Let \(\phi\) be the conjunction of \(p_{1}, p_{2}, \ldots, p_{n} .\) Prove that for any interpretation \(I, I(\phi)=T\) if and only if \(I\left(p_{i}\right)=T\) for each \(i\) such that \(1 \leq i \leq n .\) (Hint: Use induction.) (b) Let \(\phi\) be the formula $$ \left(\ldots\left(\left(p_{1} \leftrightarrow p_{2}\right) \leftrightarrow p_{3}\right) \leftrightarrow \ldots\right) \leftrightarrow p_{n} $$ for \(n \geq 1 .\) For what interpretations \(I\) is \(I(\phi)=T ?\) (Hint: The answer involves counting how many of the \(p_{i}\) 's are true in \(I\). Prove the result by induction on \(n\).)

Short Answer

Expert verified
(a) The conjunction is true when all \( p_i \) are true. (b) The biconditional formula is true for even true literals.

Step by step solution

01

Understanding the base case for conjunction

According to the problem, when \( n = 0 \), the conjunction of zero formulas is defined to be \( T \). For \( n = 1 \), the conjunction simplifies to \( p_1 \). For the base case, we need to check if the conjunction outcomes match the given initial condition: if \( n = 1 \), then \( I(\phi) = T \) if and only if \( I(p_1) = T \), which holds true by definition.
02

Inductive Hypothesis for conjunction

Assume for some \( k \geq 1 \), if \( I(\phi_k) = T \), then \( I(p_i) = T \) for every \( 1 \leq i \leq k \). \( \phi_k \) represents the conjunction of \( p_1, p_2, \dots, p_k \). This will be our inductive hypothesis.
03

Inductive Step for conjunction

We now show that if \( I(\phi_k) = T \), then it holds for \( k+1 \). The formula \( \phi_{k+1} \) is given by \( (\phi_k \wedge p_{k+1}) \). For \( I(\phi_{k+1}) = T \), it requires \( I(\phi_k) = T \) and \( I(p_{k+1}) = T \). By the inductive hypothesis, \( I(p_i) = T \) for all \( 1 \leq i \leq k \). Hence, \( I(p_i) = T \) for all \( 1 \leq i \leq k+1 \). Thus, the statement holds for \( k+1 \), completing the inductive step.
04

Base Case for biconditional formula

Consider the base case when \( n = 1 \). Here, \( \phi = p_1 \), and obviously, \( I(\phi) = T \) if and only if \( I(p_1) = T \).
05

Inductive Hypothesis for biconditional formula

Assume that for \( n = m \), the formula \( \phi_m = (\dots((p_1 \leftrightarrow p_2) \leftrightarrow p_3) \dots \leftrightarrow p_m) \) is true if and only if an even number of \( p_i \)'s (where \( 1 \leq i \leq m \)) are true.
06

Inductive Step for biconditional formula

To show the hypothesis holds for \( n = m+1 \), consider \( \phi_{m+1} = (\phi_m \leftrightarrow p_{m+1}) \). The expression \( (A \leftrightarrow B) \) is true if both are equal. For even number true at \( \phi_m \): - If \( I(p_{m+1}) = T \), then the count becomes odd, hence \( \phi_{m+1} = F \).- If \( I(p_{m+1}) = F \), then the count remains even, hence \( \phi_{m+1} = T \).Thus, the evenness or oddness switches with each successive \( I(p_i) \). This shows the parity determines \( I(\phi_{m+1}) = T \).
07

Conclusion on biconditional formula

From the inductive step, \( I(\phi) = T \) if and only if there is an even number of true \( p_i \)'s for \( n \geq 1 \). Each additional biconditional operation respects the parity of true values, reaffirming the hypothesis.

Unlock Step-by-Step Solutions & Ace Your Exams!

  • Full Textbook Solutions

    Get detailed explanations and key concepts

  • Unlimited Al creation

    Al flashcards, explanations, exams and more...

  • Ads-free access

    To over 500 millions flashcards

  • Money-back guarantee

    We refund you if you fail your exam.

Over 30 million students worldwide already upgrade their learning with Vaia!

Key Concepts

These are the key concepts you need to understand to accurately answer the question.

Conjunction
In logic, conjunction is a fundamental operation represented by the symbol \( \wedge \). It combines multiple statements into a single, composite statement.
For instance, the conjunction of statements \( p_1, p_2, \ldots, p_n \) can be visualized as cascading logical AND operations: \( ((p_1 \wedge p_2) \wedge p_3) \wedge \ldots \wedge p_n \).
This operation results in a true statement if and only if every individual component statement \( p_1, p_2, \ldots, p_n \) is true.
### Key Points on Conjunction:
  • If any component of the conjunction is false, the entire conjunction becomes false.
  • For \( n=0 \), the conjunction of zero statements is defined as true (\( T \)), which may seem counterintuitive, but serves to preserve logical consistency. This is akin to the concept of the empty product in arithmetic.
  • The conjunction operation highlights how interdependent logical statements can create comprehensive logical expressions.
Using mathematical induction provides a powerful way to prove the properties of conjunction for any number \( n \) of statements.
Biconditional
The biconditional logical operator is represented by \( \leftrightarrow \) and is a way to express equivalence between two statements.
It's true when both statements have the same truth value, i.e., when both are true or both are false. Specifically, a formula composed as \( ((p_1 \leftrightarrow p_2) \leftrightarrow p_3) \leftrightarrow \ldots \leftrightarrow p_n \) checks for a consistent pattern of truth or falsity.
### Key Properties of Biconditional:
  • When all involved statements are true or all are false, the resultant biconditional expression is true.
  • The biconditional checks parity in a sequence of truths and observantly tracks parity flips as it processes each consequent operator.
  • This operation can be used in proofs requiring precise logical equivalences.
An inductive approach reveals the condition under which such complex biconditional structures yield a true value—specifically, that an even number of statements are true among any finite collection \( p_i \). This intrinsic sensitivity to evenness or oddness plays a crucial role in constructing logical proofs involving such operators.
Truth Assignment
In propositional logic, a truth assignment is a method of determining the truth or falsity of each variable within a logical expression.
It's a vital concept used to assess the outcome of logical expressions under various conditions. Each variable within a formula can either be assigned true (\( T \)) or false (\( F \)), and these assignments can significantly change the result of complex logical constructs.
### How Truth Assignment Works:
  • Truth assignments are foundational, as they provide the basis for evaluating logical statements.
  • Each formula under consideration is interpreted according to the given truth assignment, which determines the overall truth value of the formula.
  • For any induction on logical expressions, such as conjunctions or biconditionals, truth assignments are key to comparing initial assumptions with new outcomes.
A deep understanding of truth assignments is crucial for working effectively with logical expressions, enabling a deeper comprehension of deductive reasoning and the mechanics underlying logical proofs.

One App. One Place for Learning.

All the tools & learning materials you need for study success - in one app.

Get started for free

Most popular questions from this chapter

(a) Find the resolvant of \((p \vee q)\) and \((\neg p \vee r)\) on \(p\). (b) Find the resolvant of \((p \vee q \vee r \vee s)\) and \((\neg p \vee \neg q \vee t)\) on \(p\). (c) Find the resolvant of \((p \vee q)\) and \(\neg p\) on \(p\). (d) Find the resolvant of \((p)\) and \((\neg p)\) on \(p\). (e) Which resolvant above from parts (a) through (d) is a tautology? Which is tautologically false?

Write the truth tables for the following formulas, Use the truth table to determine whether any of these formulas is a tautology. (a) \(((p \rightarrow q) \wedge(q \rightarrow r)) \rightarrow(p \leftrightarrow r)\) (b) \(((p \rightarrow q) \wedge(q \rightarrow r)) \rightarrow(p \rightarrow r)\) (c) \(((p \rightarrow q) \rightarrow r) \rightarrow(p \rightarrow(q \rightarrow r))\) (d) \((p \rightarrow(r \vee q)) \rightarrow((p \rightarrow r) \vee(p \rightarrow q))\) (e) \((p \rightarrow(r \wedge q)) \rightarrow((p \rightarrow r) \vee(p \rightarrow q))\) (f) \(((p \rightarrow q) \rightarrow q) \rightarrow p\)

For each quantified formula that follows: find a universe \(U\) and predicates \(A\) and \(B\) in which the formula is true and \(U, A\) and \(B\) in which it is false. (a) \(\forall x(((A(x) \vee B(x)) \wedge \neg(A(x) \wedge B(x)))\) (b) \(\forall x \forall y(P(x, y) \rightarrow P(y, x))\) (c) \(\forall x(P(x) \rightarrow \exists y Q(x, y))\) (d) \(\exists x(A(x) \wedge \forall y B(x, y))\) (e) \(\forall x A(x) \rightarrow(\forall x B(x) \rightarrow(\forall x(A(x) \rightarrow B(x))))\)

Find the expression tree for the formula $$ ((\neg(p \wedge q)) \vee(\neg(q \wedge r))) \wedge((\neg(p \leftrightarrow(\neg(\neg s)))) \vee((r \wedge s) \vee(\neg q))) . $$ Evaluate the expression tree if proposition \(p\) is \(F\), proposition \(q\) is \(T\), proposition \(r\) is \(F\), and proposition \(s\) is \(T\).

The first stage of the method described to "push negations inward" was a method to climinate \(\rightarrow\) 's and \(\leftrightarrow\) 's. Prove that in the method to eliminate them, the process of substituting always stops, Consider, for example, the substitution in the formula $$ (p \leftrightarrow q) \leftrightarrow(r \leftrightarrow s) $$ If the substitution is first performed on the second \(\leftrightarrow\), the resultant formula is $$ ((p \leftrightarrow q) \rightarrow(r \leftrightarrow s)) \wedge((r \leftrightarrow s) \rightarrow(p \leftrightarrow q)) $$ which has more \(\leftrightarrow\) 's to replace than in the original formula! At first sight, one might expect that if the substitutions are made in the wrong order, the process might continue generating more \(\leftrightarrow\) 's at each stage, and the process might continue forever. (Hint: One method is to, instead of just counting the number of \(\leftrightarrow\) symbols, put a weight on each \(\leftrightarrow\) symbol, with the weight of the \(\leftrightarrow\) symbol in \(\psi \leftrightarrow x\) being dependent on the number of \(\leftrightarrow\) 's in \(\psi\) and \(\chi\). If the correct method of calculating weights is used, it can be shown that the total weight of the \(\leftrightarrow\) 's decreases with each substitution.

See all solutions

Recommended explanations on Computer Science Textbooks

View all explanations

What do you think about this solution?

We value your feedback to improve our textbook solutions.

Study anywhere. Anytime. Across all devices.

Sign-up for free